Reconstruction of Environmental Fiqh Language Based on Tazkiyatun Nafs: a Sufistic Approach to Students' Mental Health - Muhammad Amiruddin (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2026)
This study proposes the construction of environmental fiqh language within Islamic boarding schools (pesantren) as an integrative framework to shape Generation Z characterized by tazkiyatun nafs, Sufi orientation, and psychological well-being. Employing a qualitative interpretative approach with a multi-site design across several pesantren in Indonesia, data were collected through limited participatory observation, semi-structured interviews, and document analysis. The data were analyzed using thematic-critical and religious discourse analysis. The findings demonstrate that eco-theological language in pesantren operates as a semiotic-performative system that not only transmits theological knowledge but also internalizes ecological values through daily practices. The integration of tawhid, environmental ethics, and spiritual practices fosters faith-based ecological awareness while strengthening students' self-regulation and emotional stability. The novelty of this study lies in formulating environmental fiqh language as a psycho-spiritual eco-systemic model that integrates linguistic, theological, and mental health dimensions into a coherent analytical framework. This model positions pesantren as a living laboratory for developing sustainability ethics grounded in Islamic spirituality. The study contributes to the advancement of pesantren-based eco-theosophy and offers an alternative paradigm in global sustainability discourse rooted in transcendental values.